2014
DOI: 10.2147/aabc.s63749
|View full text |Cite
|
Sign up to set email alerts
|

In silico predictive model to determine vector-mediated transport properties for the blood–brain barrier choline transporter

Abstract: The blood–brain barrier choline transporter (BBB-ChT) may have utility as a drug delivery vector to the central nervous system (CNS). We therefore initiated molecular docking studies with the AutoDock and AutoDock Vina (ADVina) algorithms to develop predictive models for compound screening and to identify structural features important for binding to this transporter. The binding energy predictions were highly correlated with r2=0.88, F=692.4, standard error of estimate =0.775, and P-value<0.0001 for selected B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 41 publications
(56 reference statements)
2
127
0
1
Order By: Relevance
“…The resulting binding energy of the docked structure was found to be -3.86 kcal/mol, which is quite low. [57] Interestingly, redocking using Autodock vina program [58] produced similar results (binding affinity -3.9 kcal/mol with selectivity towards minor grooves, Fig. S3 supplementary information), indicating the accuracy of the tool as well affinity of the probes towards a biopolymer.…”
Section: Docking Studiesmentioning
confidence: 71%
“…The resulting binding energy of the docked structure was found to be -3.86 kcal/mol, which is quite low. [57] Interestingly, redocking using Autodock vina program [58] produced similar results (binding affinity -3.9 kcal/mol with selectivity towards minor grooves, Fig. S3 supplementary information), indicating the accuracy of the tool as well affinity of the probes towards a biopolymer.…”
Section: Docking Studiesmentioning
confidence: 71%
“…However, we independently found through 14 molecular modeling, molecular dynamics and docking simulations that 6-aminocholestanol 15 could target the L. infantum LieIF4A protein, which is a probable ortholog of the translation-16 initiation factor eIF4A [20, 23]. Moreover, it shows structural similarity to the previously 17 characterized hippuristanol that is an allosteric inhibitor of RNA binding in eukaryotic 18 eIF4A-like proteins that locks the RecA-like domains in a nonproductive closed conformation 19 [19]. 20…”
Section: Discussionmentioning
confidence: 99%
“…The 24 top hit compounds were investigated for their interaction with the active site's residues and ranked in term of the free energy of binding (ΔG bind = -10 kcal/mol to -5 kcal/mol, see S1 Table. We identified that there are more than 50 ligands docked into the active site with that ΔG bind range, but only 24 of them shows interesting interactions with the essential amino acid residues. The selection of ΔG bind range is adopted from the study reported by Shityakov (2014) that Gibbs free energy of binding < 6.0 kcal/mol is clustered as active when this prediction is highly correlated with the experimental results with R 2 = 0.880; F = 692.4 standard error of estimate = 0.775 and p-value = 0.0001 [58]. This virtual screening study has a limitation in which no decoy database is being used to validate the docking protocol.…”
Section: Virtual Screening and The Confirmation Of Activity Of The Inmentioning
confidence: 99%